Asthma does not influence the severity of COVID-19: a meta-analysis. (3rd June 2022) - Wu, Ting; Yu, Pengyi; Li, Yuanxia; Wang, Junxin; Li, Zhen; Qiu, Jingjing; Cui, Limei; Mou, Yakui; Sun, Yan
Abstract: Objective: Previous studies have reported a correlation between coronavirus disease-2019 (COVID-19) and asthma. However, data on whether asthma constitutes a risk factor for COVID-19 and the prevalence of asthma in COVID-19 cases still remain scant. Here, we interrogated and analyzed the association between COVID-19 and asthma. Methods: In this study, we systematically searched PubMed, Embase, and Web of Science databases for studies published between January 1 and August 28, 2020. We included studies that reported the epidemiological and clinical features of COVID-19 and its prevalence in asthma patients. We excluded reviews, animal trials, single case reports, small case series and studies evaluating other coronavirus-related illnesses. Raw data from the studies were pooled into a meta-analysis. Results: We analyzed findings from 18 studies, including asthma patients with COVID-19. The pooled prevalence of asthma in COVID-19 cases was 0.08 (95% CI, 0.06–0.11), with an overall I 2 of 99.07%, p  < 0.005. The data indicated that asthma did not increase the risk of developing severe COVID-19 (odds ratio [OR] 1.04 (95% CI, 0.75-1.46) p  = 0.28; I 2 =20%). In addition, there was no significant difference in the incidence of asthma with age in COVID-19 infections [OR] 0.77(95% CI, 0.59–1.00) p  = 0.24; I 2 =29%). Conclusion: Taken together, our data suggested that asthma is not a significant risk factor for the development of severe COVID-19.